Designing measures of complex collaborations with participatory, evidence-centered design - Farrell, Caitlin C.; Penuel, William R.; Arce-Trigatti, Paula; Soland, James; Singleton, Corinne; Resnick, Alison Fox; Stamatis, Kristina; Riedy, Robbin; Henrick, Erin; Sexton, Stacey; Wellberg, Sarah; Schmidt, Danny (Frontiers in Research Metrics and Analytics, 2024)
An increasingly popular form of collaboration involves forming partnerships among researchers, educators, and community members to improve or transform education systems through research inquiry. However, not all partnerships are successful. The field needs valid, reliable, and useful measures to help with assessing progress towards partnership goals. In this community case study, we present a participatory, mixed-methods approach for creating measures to assess the progress of education research-practice partnerships (RPPs). The case illustrates a novel approach to measurement design, driven by perspectives and feedback of over 300 members of 80 partnerships. As a result, the measures align with the values and practices of the very collaborations the measures were intended to assess.This project sits at the crossroads of multiple traditions and fields. It joins a growing literature base in evaluation that looks at relationships as an asset for effectiveness (Bright et al., 2016;Brinkerhoff, 2002;Pisacane & Tagliacozzo, 2023). It contributes to literature that identifies strategies for assessing the benefits of cross-sector partnerships (Koontz & Thomas, 2012;Van Tulder et al., 2016). It extends insights on the process and outcomes of collaborative research efforts, as well (e.g.,